Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Kretiva Surya Pratama Bandung - Ahmad Firmansyah; Eki Dudi Darmawan (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this study was to determine whether the effect of job satisfaction (x) affects the performance of employees (y) at PT. Kreativa Surya Pratama Bandung subsidiary from Telkom Indonesia for Marketing or Marketing. The population is 237 people. This study uses quantitative methods. By using the reference calculation of the Slovin formula, which is as many as 70 respondents, the calculations in this research use the SPSS application. The data analysis technique in this study used a simple linear regression test. Based on the results of research and discussion, it can be concluded that job satisfaction has a partially significant effect on employee performance. This result is based on the t-value of 9.170 and the t-table of 1.995 having a sig value of 0.001 < 0.05. With the acquisition of t-count greater than t-table (9,170 > 1,995). the coefficient of determination of the value of adjusted r square shows the results of 0.549 or 54.9%, so from the results of the coefficient value 54.9% is influential while the remaining 45.1% is influenced by other factors.